Cognitive Effects of Toxoplasma and CMV Infections: A Cross-Sectional Study of 557 Young Adults Considering Modulation by Sex and Rh Factor - Flegr, Jaroslav; Chvátalová, Veronika; Příplatová, Lenka; Tureček, Petr; Kodym, Petr; Šebánková, Blanka; Kaňková, Šárka (Pathogens (Basel, Switzerland), 2024)
One-third of humanity harbors a lifelong infection with Toxoplasma gondii, and probably about 80% are infected with human cytomegalovirus (CMV). This study aims to delineate the associations between toxoplasmosis and cognitive abilities and compare these to the associations with CMV. We evaluated the cognitive performance of 557 students, who had been examined for Toxoplasma and CMV infections, using intelligence, memory, and psychomotor tests. The results indicated cognitive impairments in seropositive individuals for both pathogens, with variations in cognitive impact related to sex and the Rh factor. Specifically, Toxoplasma infection was associated with lower IQ in men, whereas CMV was predominantly associated with worse performance by women when testing memory and reaction speeds. Analysis of the antibody concentrations indicated that certain Toxoplasma-associated cognitive detrimental effects may wane (impaired intelligence) or worsen (impaired reaction times) over time following infection. The findings imply that the cognitive impairments caused by both neurotropic pathogens are likely due to pathological changes in the brain rather than from direct manipulative action by the parasites.
Keywords: Young Adult; Cross-Sectional Studies; Rh-Hr Blood-Group System; Toxoplasma; Male; Cytomegalovirus Infections; mladý dospělý; psychomotor performance; toxoplasmosis; Adolescent; sexuální faktory; parasite; behavior; Adult; dospělí; toxoplazmóza; mužské pohlaví; cognition; cytomegalovirové infekce; mladiství; krevní skupiny - systém Rh-Hr; cytomegalovirus; kognice; lidé; Toxoplasmosis; ženské pohlaví; intelligence; Humans; Rh factor; Sex Factors; průřezové studie; Cytomegalovirus; manipulation hypothesis; Female; memory; Cognition